PENGENALAN MATERI DASAR AKUNTANSI UNTUK PEMBELAJARAN DI SMA TARSISIUS 1 - Heni; Sriwati (Jurnal Serina Abdimas, 2024)
Accounting education at the high school level plays a crucial role in equipping students with essential skills that are useful, both for continuing their studies at university and for entering the workforce. The Community Service Activity (PKM) conducted at SMA Tarsisius 1 Jakarta aims to introduce basic accounting concepts through an extracurricular program. This program is designed to provide an in-depth understanding of accounting fundamentals, starting from the history of accounting, the occurrence of transactions, the recording of transactions, to the preparation of the trial balance. The teaching methods used include theory, exercises, and evaluations through quizzes and educational games tailored to the students' needs. The use of interactive teaching methods is expected to enhance students' understanding of basic accounting concepts. The evaluation conducted showed an improvement in students' understanding, measured through quiz results and satisfaction surveys. The evaluation results indicate that this program is able to prepare students to continue their education in the field of accounting, while also equipping them with skills that can be applied in daily life or in the workplace. The program also aims to foster students' interest in accounting, as well as provide them with practical skills in proper and correct financial management. It is hoped that by introducing basic accounting concepts at an early stage, students will be better prepared to face academic and professional challenges in the future. The development of accounting skills through this program also has a positive impact on students' readiness to meet career demands in the business world and small to medium enterprises. ABSTRAK Pendidikan akuntansi di tingkat SMA memiliki peranan krusial dalam membekali siswa dengan keterampilan dasar yang berguna, baik untuk melanjutkan studi ke perguruan tinggi maupun untuk memasuki dunia kerja. Kegiatan Pengabdian Kepada Masyarakat (PKM) yang dilaksanakan di SMA Tarsisius 1 Jakarta bertujuan untuk memperkenalkan konsep dasar akuntansi melalui program ekstrakurikuler. Program ini dirancang untuk memberikan pemahaman mendalam tentang dasar-dasar akuntansi, mulai dari sejarah akuntansi, terjadinya transaksi, pencatatan transaksi hingga penyusunan neraca saldo. Metode pengajaran yang digunakan meliputi teori, latihan soal, serta evaluasi melalui kuis dan permainan edukatif yang disesuaikan dengan kebutuhan siswa. Penggunaan metode pembelajaran interaktif diharapkan dapat meningkatkan pemahaman siswa terhadap konsep dasar akuntansi. Evaluasi yang dilakukan menunjukkan adanya peningkatan pemahaman siswa, yang diukur melalui hasil kuis dan survei kepuasan. Hasil evaluasi menunjukkan bahwa program ini mampu mempersiapkan siswa untuk melanjutkan pendidikan di bidang akuntansi, sekaligus membekali mereka dengan keterampilan yang dapat diterapkan dalam kehidupan sehari-hari maupun dunia kerja. Program ini juga bertujuan untuk menumbuhkan minat siswa terhadap akuntansi, serta memberikan mereka keterampilan praktis dalam pengelolaan keuangan yang baik dan benar. Diharapkan, dengan diperkenalkannya konsep dasar akuntansi sejak dini, siswa akan lebih siap menghadapi tantangan akademis dan profesional di masa depan. Pengembangan keterampilan akuntansi melalui program ini juga memberikan dampak positif terhadap kesiapan siswa dalam menghadapi tuntutan karier di dunia bisnis maupun usaha kecil menengah.